Measuring Peace of Heart: The Development and Validation of Taṭmainn al-Qulūb Scale (TQS) - Ahmad Rusdi; Rumiani Rumiani; Nyda Afsari; Rena Latifa (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2022)
Peace of heart is an inner spiritual experience that generates an emotional feeling of harmony. Peace of heart (taṭmainn al-qulūb) is an important aspect applicable for the life of the Muslim community as a treatment for the psychological problems of the modern era, mainly due to the absence of peace. Thus far, no research has been done on the development of peace of heart to capture the uniqueness, specific aspect, and distinctive aspect of peace in Muslim community. A total of 744 respondents responded to this research. Six experts were involved to examine item wording in this research (CVR= .67-1.00). This study has found that the TQS consists of two components (al-sukūn and al-yaqīn) with a good loading factor (.687-.884), Cronbach's Alpha (.844), and item consistency (.545-.857). All items had a good difficulty level and appropriate rating. Convergence validity on this scale was indicated by its correlation with The Brief Serenity Scale (r= .612). The criterion-related validity on this scale was indicated by its correlation with dhikr quality (r= .629), Islamic positive religious coping (r= .518), perceived stress (r= -.453), and sensibility (r= .103). Further studies need to be done based on the followings: 1) Examining the measurement on this topic with larger respondents having equal variance; 2) Considering gender, education level, and age in norming study of this scale; 3) Validating with other measurements to add validity information, especially discriminant validity